THOUGHTS OF K.H. ABDUL MALIK KALAM FREE WILL AND FREE ACT ANALYSIS OF THE BOOK OF NADHARAT AL-AFKAR - Faizin; Daflaini (Qawwam : The Leader's Writing, 2025)
K.H. Abdul Malik's thoughts on free will and free act in the Book of Nadharat al-Afkar offer a moderate theological approach in explaining the relationship between divine will and human freedom. This study aims to analyze the concepts of free will and free act formulated by K.H. Abdul Malik and their relevance to Islamic theological discourse and the lives of Muslims today. K.H. Abdul Malik adopted a synthesis approach, combining the view between Jabariyah determinism and Qadariyah's absolute freedom. He emphasized that humans have efforts as a form of free will, but human actions remain within the scope of God's will and permission. Through the concept of kasb, he shows human responsibility for his actions while placing it within the framework of God's will.The results of the analysis show that this view reflects an effort to bring harmony between the aspects of classical theology and the challenges of modern life. K.H. Abdul Malik's thinking is relevant in providing a theological foundation for Muslims to understand individual freedom without neglecting responsibility to God. This study reinforces the importance of kalam thinking in responding to contemporary problems and offers a balanced perspective between human effort and submission to the divine will.